2020
DOI: 10.3847/1538-4365/ab672d
|View full text |Cite
|
Sign up to set email alerts
|

The Radial Dependence of Proton-scale Magnetic Spectral Break in Slow Solar Wind during PSP Encounter 2

Abstract: Magnetic field fluctuations in the solar wind are commonly observed to follow a power law spectrum. Near proton-kinetic scales, a spectral break occurs which is commonly interpreted as a transition to kinetic turbulence. However, this transition is not yet entirely understood. By studying the scaling of the break with various plasma properties, it may be possible to constrain the processes leading to the onset of kinetic turbulence.Using data from Parker Solar Probe (PSP), we measure the proton scale break ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 64 publications
10
30
0
Order By: Relevance
“…According to Figure 4, on the other hand, there appears an increasing trend of kρ p with β ‖ p for a given slope or | σ k |. Such a trend may be related to the increasing trend of k b ρ p (dimensionless spectral break position) with β ‖ p , as found by Duan et al (2020).…”
Section: Statistical Resultssupporting
confidence: 59%
“…According to Figure 4, on the other hand, there appears an increasing trend of kρ p with β ‖ p for a given slope or | σ k |. Such a trend may be related to the increasing trend of k b ρ p (dimensionless spectral break position) with β ‖ p , as found by Duan et al (2020).…”
Section: Statistical Resultssupporting
confidence: 59%
“…Duan et al. (2020) have shown that in the Alfvénic slow wind the break manifests a radial dependence similar to fast wind, with the spectral break occurring around the ion cyclotron resonance scales (Bruno & Trenchi, 2014; D’Amicis, Matteini, & Bruno, 2019). A similarity between fast and Alfvénic slow wind is also recovered in the relation between β ∥ and T ⊥ / T ∥ , suggesting that Alfvénic slow wind is characterized by more anisotropic distribution functions than non‐Alfvénic slow wind, as is also seen in the fast solar wind (J. Huang, et al., 2020), and in agreement with observations at 1 AU (D’Amicis, Matteini, & Bruno, 2019).…”
Section: In Situ Observationsmentioning
confidence: 99%
“…The statistical properties of the solar wind generally vary with speed, location, and type of source region and heliocentric distance (Bavassano et al 1982;Tu et al 1989;He et al 2013;Matteini et al 2014;Horbury et al 2018;Perrone et al 2019;Wang et al 2019;Bandyopadhyay et al 2020;Chen et al 2020;Chhiber et al 2020;Duan et al 2020;Qudsi et al 2020). Tu et al (1989) contrast the properties of magnetohydrodynamic (MHD) turbulence between highspeed and low-speed solar wind at 0.3 au using the spectra of Elsässer variables, cross helicity, residual energy, Alfvén ratio, and Elsässer ratio.…”
Section: Introductionmentioning
confidence: 99%